Use of fortified pied de cuve as an innovative method to start spontaneous alcoholic fermentation for red winemaking. (16th October 2015) - Moschetti, G.; Corona, O.; Gaglio, R.; Squadrito, M.; Parrinello, A.; Settanni, L.; Barone, E.; Francesca, N.
Abstract: Background and Aims: Some wineries, in order to promote the growth of yeasts able to ferment grape musts, traditionally produce wines using the 'pied de cuve' method. The aim of the present work was to study the performance of fortified pied de cuve (FPdC) prepared by addition of wine. Method and Results: Two FPdCs were prepared with the addition of wine at 1.5 and 3% (v/v) of ethanol to the musts and allowed to spontaneously ferment. The FPdCs were then added to fresh bulk musts in order to accelerate the spontaneous alcoholic fermentation (AF). Interestingly, several S accharomyces cerevisiae strains isolated during the pied de cuve preparation were detected at the highest concentration throughout AF. The chemical composition of the wines conformed to commercial regulations. The volatile organic compounds (VOCs) were mainly represented by diethyl succinate and ethyl lactate, as well as by hexanol and isoamyl alcohol. Principal component analysis of the chemical parameters, VOCs and sensory data showed that the use of experimental pied de cuve influenced positively the composition of the final wines. Conclusion: The FPdC had no negative impact on the microbiological and chemical composition of wines, but it affected the diversity of the species S . cerevisiae present during AF and the sensory profile of the final wine. Significance of the Study: This study provided evidence that FPdC accelerates spontaneous AF and influences the sensory profile of red wines.